The child in post-apocalyptic cinema - Olson, Debbie C., 1961- (Lexington Books, 2015)
This collection explores and interrogates the complex role of the child character in the dystopian landscape of post-apocalyptic cinema, including classic, recent, and international films, approached from a variety of theoretical, methodological, and cultural perspectives.